MODERN CONCEPTS AND EPIDEMIOLOGICAL ASPECTS OF BRUCELLOSIS - Djabbarova N.R.; Daminov F.A.; Usmonova Y.; Husanova M. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Among more than 180 nosological forms of zoonotic infectious diseases, brucellosis remains significant due to the scale of economic damage to livestock and public health. Brucellosis is an infectious, particularly dangerous zoonotic disease caused by bacteria of the genus *Brucella*, which is transmitted from animals to humans and is characterized by a severe and often chronic course [1, 8].